2021
DOI: 10.1007/s11883-021-00973-w
|View full text |Cite
|
Sign up to set email alerts
|

Moving the Needle on Atherosclerotic Cardiovascular Disease and Heart Failure with Influenza Vaccination

Abstract: Purpose of Review The interplay between viral respiratory infections and cardiovascular disease has been most comprehensively researched using seasonal and pandemic influenza viruses as case studies. Here, we summarize the latest international observational research and clinical trials that examined the association between influenza, influenza vaccines, and cardiovascular disease, while contextualizing their findings within those of landmark studies. Recent Findings Mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 82 publications
0
6
1
Order By: Relevance
“…[23] Moreover, the authors did not find significant differences in the WHO functional class deterioration and presence of concomitant disease between vaccinated and unvaccinated patients. Unlike previous studies, [23][24][25] in which patients with chronic diseases had higher vaccine acceptance than the general population, our study revealed the opposite: patients with PH exhibited a higher hesitancy rate (271/706, 38.4%) than the general Chinese population (422/2377, 17.8%). [26] In our study, patients with worse disease status were more reluctant to receive vaccination than their counterparts.…”
Section: Discussioncontrasting
confidence: 99%
“…[23] Moreover, the authors did not find significant differences in the WHO functional class deterioration and presence of concomitant disease between vaccinated and unvaccinated patients. Unlike previous studies, [23][24][25] in which patients with chronic diseases had higher vaccine acceptance than the general population, our study revealed the opposite: patients with PH exhibited a higher hesitancy rate (271/706, 38.4%) than the general Chinese population (422/2377, 17.8%). [26] In our study, patients with worse disease status were more reluctant to receive vaccination than their counterparts.…”
Section: Discussioncontrasting
confidence: 99%
“…The association between influenza infection and major CV events is well recognized and has been repeatedly confirmed over the years in epidemiological studies [ 8 , 34 , 35 ]. The link between viral respiratory infections and cardiovascular disease (CVD) is bidirectional.…”
Section: Impact Of Influenza On High-risk Populations and Benefits Of...mentioning
confidence: 97%
“…T-helper 1 (Th1) cells are responsible for the production of pro-inflammatory cytokines, including interferon-gamma (IFN-gamma). These cytokines play a crucial role in promoting inflammation and contributing to the destabilization of plaque [ 13 ]. T-helper 2 (Th2) cells, conversely, secrete anti-inflammatory cytokines, including IL-4 and IL-10, which potentially play a protective role in restricting the advancement of plaque.…”
Section: Reviewmentioning
confidence: 99%